Subthalamic nucleus deep brain stimulation with a multiple independent constant current-controlled device in Parkinson's disease (INTREPID): a multicentre, double-blind, randomised, sham-controlled study. Issue 6 (June 2020) - Vitek, Jerrold L; Jain, Roshini; Chen, Lilly; Tröster, Alexander I; Schrock, Lauren E; House, Paul A; Giroux, Monique L; Hebb, Adam O; Farris, Sierra M; Whiting, Donald M; Leichliter, Timothy A; Ostrem, Jill L; et al.
Summary: Background: Deep brain stimulation (DBS) of the subthalamic nucleus is an established therapeutic option for managing motor symptoms of Parkinson's disease. We conducted a double-blind, sham-controlled, randomised controlled trial to assess subthalamic nucleus DBS, with a novel multiple independent contact current-controlled (MICC) device, in patients with Parkinson's disease. Methods: This trial took place at 23 implanting centres in the USA. Key inclusion criteria were age between 22 and 75 years, a diagnosis of idiopathic Parkinson's disease with over 5 years of motor symptoms, and stable use of anti-parkinsonian medications for 28 days before consent. Patients who passed screening criteria were implanted with the DBS device bilaterally in the subthalamic nucleus. Patients were randomly assigned in a 3:1 ratio to receive either active therapeutic stimulation settings (active group) or subtherapeutic stimulation settings (control group) for the 3-month blinded period. Randomisation took place with a computer-generated data capture system using a pre-generated randomisation table, stratified by site with random permuted blocks. During the 3-month blinded period, both patients and the assessors were masked to the treatment group while the unmasked programmer was responsible for programming and optimisation of device settings. The primary outcome was the difference in mean change from baseline visit to 3 months post-randomisation between the active and control groups in the mean number of waking hours per day with good symptom control and no troublesome dyskinesias, with no increase in anti-parkinsonian medications. Upon completion of the blinded phase, all patients received active treatment in the open-label period for up to 5 years. Primary and secondary outcomes were analysed by intention to treat. All patients who provided informed consent were included in the safety analysis. The open-label phase is ongoing with no new enrolment, and current findings are based on the prespecified interim analysis of the first 160 randomly assigned patients. The study is registered with ClinicalTrials.gov, NCT01839396 . Findings: Between May 17, 2013, and Nov 30, 2017, 313 patients were enrolled across 23 sites. Of these 313 patients, 196 (63%) received the DBS implant and 191 (61%) were randomly assigned. Of the 160 patients included in the interim analysis, 121 (76%) were randomly assigned to the active group and 39 (24%) to the control group. The difference in mean change from the baseline visit (post-implant) to 3 months post-randomisation in increased ON time without troublesome dyskinesias between the active and control groups was 3·03 h (SD 4·52, 95% CI 1·3–4·7; p<0·0001). 26 serious adverse events in 20 (13%) patients occurred during the 3-month blinded period. Of these, 18 events were reported in the active group and 8 in the control group. One death was reported among the 196 patients before randomisation, which was unrelated to the procedure, device, or stimulation. Interpretation: This double-blind, sham-controlled, randomised controlled trial provides class I evidence of the safety and clinical efficacy of subthalamic nucleus DBS with a novel MICC device for the treatment of motor symptoms of Parkinson's disease. Future trials are needed to investigate potential benefits of producing a more defined current field using MICC technology, and its effect on clinical outcomes. Funding: Boston Scientific.